Transport as a factor of sustainability of national economy - Duchoň, Bedřich (Univerzita Pardubice, 2010)
Microeconomic level can study of entrepreneurial subject and his/her decisions. Economic subject takes location decision and final choice as a function of transport possibilities and availability. Macroeconomic point of view involves structure and level of economic activities in geographical areas, cities, regions and countries, especially as a function of quality, safety and other factors. The proposal is aimed at microeconomics and macroeconomics problem of transport.
Keywords: economic growth; competition; industry; transport; microeconomics; national economy